The PARAChute Project: Remote Monitoring of Posture and Gait for Fall Prevention. (23rd April 2007) - Hewson Hewson, David J. David J.; Duchêne Duchêne, Jacques Jacques; Charpillet Charpillet, François François; Saboune Saboune, Jamal Jamal; Michel-Pellegrino Michel-Pellegrino, Valérie Valérie; Amoud Amoud, Hassan Hassan; Doussot Doussot, Michel Michel; Paysant Paysant, Jean Jean; Boyer Boyer, Anne Anne; Hogrel Hogrel, Jean-Yves Jean-Yves
Abstract : Falls in the elderly are a major public health problem due to both their frequency and their medical and social consequences. In France alone, more than two million people aged over 65 years old fall each year, leading to more than 9 000 deaths, in particular in those over 75 years old (more than 8 000 deaths). This paper describes the PARAChute project, which aims to develop a methodology that will enable the detection of an increased risk of falling in community-dwelling elderly. The methods used for a remote noninvasive assessment for static and dynamic balance assessments and gait analysis are described. The final result of the project has been the development of an algorithm for movement detection during gait and a balance signature extracted from a force plate. A multicentre longitudinal evaluation of balance has commenced in order to validate the methodologies and technologies developed in the project.